In vitro and in vivo aphrodisiac properties of the seed extract from Allium tuberosum on corpus cavernosum smooth muscle relaxation and sexual behavior parameters in male Wistar rats - Xingli Tang; Opeyemi J. Olatunji; Yifeng Zhou; Xilin Hou (BMC, 2017)
Abstract Background Allium tuberosum is a well-known spice as well as a herb in traditional Chinese medicine, used for increasing libido and treating erectile dysfunction. However, not many studies have been done to evaluate the sexual enhancing properties of A. tuberosum. The aim of this study was to evaluate the aphrodisiac and vasorelaxant properties of A. tuberosum on corpus cavernosum smooth muscle (CCSM) as well as checking the effect on enhancing male rat sexual behavior, libido, potency as well as its spermatogenic properties. Method The seeds were powdered and sequentially extracted with hexane, ethyl acetate and butanol. Male Wistar rats were administered with graded doses of the n-BuOH extracts (ATB) of A. tuberosum (50, 100, 200 and 400 mg/kg) and Viagra was used as the positive control drug. The extract/drug was administered by gastric probe once daily for 45 days and the sexual behavior was analyzed by exposing the male rats to female rats in the estrus period. Results ATB relaxed corpus cavernosum smooth muscle (68.9%) at a concentration of 200 μg/ml. The results obtained from the animal studies indicated that ATB significantly increased mount frequency (MF), intromission frequency (IF), ejaculation frequency (EF), ejaculation latency (EL) and markedly reduced post ejaculatory interval (PEI), mount latency (ML), and intromission latency (IL). Furthermore, a remarkable increase in the test for potency was observed as witnessed by marked increase in erections, quick flips, long flips and total reflex. In addition, ATB significantly improved the sperm viability and count as well as increased the concentrations of testosterone, follicle stimulating hormone (FSH), and phosphatases in the treated animals. Conclusion Thus our results suggest that A. tuberosum could stimulate sexual arousal and enhance sexual execution in male rats, thus providing valuable experimental evidence that A. tuberosum possesses sexual enhancing properties.